Vice, crime and poverty : how the Western imagination invented the underworld - Kalifa, Dominique; Emanuel, Susan (New York : Columbia University Press, 2019)
"Prostitutes, criminals, and the sordid, dangerous places they inhabit have always been with us. Yet there has not always been an "underworld," or what the French call "les bas-fonds." This expression, which appeared in most western languages in the 19th century, reveals a new way of looking at these social ills and raises a key historical question: why did the century that gave us positivism, industry, democratization, and mass culture name--and thus reframe--its view of its social margins? This book explores this imaginary. It shows how the underworld came into being in the shattered Europe of the 19th century, born of a tradition in which biblical symbols-Sodom, Gomorrah, Babylon-intermingled with the "bad poor" of Christian lore and images of modern roguery like the Cour des Miracles. It decodes the construction of a worldview that has never ceased to fascinate us. For while it connotes things that are real-poverty, crime, and transgressions of all sorts-the "underworld" also constitutes an imaginary that expresses our fears, our anxieties, our desires. In representing the nether regions of our society-its "accursed share" so to speak-it also provides a route of symbolic and social escape. Although many of its components still exist or have been readapted to new contexts, the specific combination that arose in connection with the 19th century underworld gradually faded away in the 20th century. The welfare states established in the wake of the Second World War left very little room for it. And yet, while the contexts have changed, both the debates on issues related to the "underclass" and the images in contemporary cinema and steampunk culture reveal that the shadow of the underworld still lurks all around us"--
In the den of horror -- Courts of miracles -- "Dangerous classes" -- Empire of lists -- The disguised prince -- The grand dukes' tour -- Poetic flight -- Ebbing of an imaginary -- Slow eclipse of the underworld -- Persistent shadows -- Roots of fascination
Print version record
Includes bibliographical references and index
Translation of: Bas-fonds
In English.
JSTOR
Keywords: Urban poor -- History; Marginality, Social; Marginality, Social, in literature; Criminals -- History; Criminals in literature; Inner cities -- History; Crime -- History; Inner cities in literature; Social representations; Deviant behavior in literature; Pauvres en milieu urbain -- Histoire; Criminels -- Histoire; Criminels dans la littérature.; Représentations sociales; Déviance dans la littérature.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Europe -- Western; Crime; Criminals; Criminals in literature; Deviant behavior in literature; Inner cities; Inner cities in literature; Marginality, Social; Marginality, Social, in literature; Social representations; Urban poor; History